Factors Affecting Rice Prices in Indonesia (Production, Consumption, Imports, International Prices, Crop Damage) - Ugi Sugiharto (International Journal of Economics and Management Sciences, 2024)
Rice prices in Indonesia have experienced significant fluctuations from 2019 to 2023, influenced by factors such as production, consumption, imports, international prices, and crop damage. The highest rice production was recorded in 2022 at 31,540,522 tons, while the lowest production occurred in 2023 at 31,101,285 tons. The highest rice consumption was in 2023 at 30,616,081 tons, and the lowest was in 2019 at 28,930,000 tons. The highest rice imports were in 2023 at 2,715,854 tons, and the lowest was in 2019 at 6,197 tons. Global rice prices also fluctuated, ranging from Rp. 6,674/kg in 2019 to Rp. 8,667/kg in 2023. Crop damage was lowest in 2022 at 470,131 hectares and highest in 2019 at 819,444 hectares. It's important to note that the fluctuations in rice prices are intensely influenced by several factors that highlight the need for effective price stabilization policies to guarantee the accessibility and affordability of rice for the public.